2000
DOI: 10.1067/mva.2000.107573
|View full text |Cite
|
Sign up to set email alerts
|

Endovenous management of saphenous vein reflux

Abstract: Closure treatment is clinically effective, albeit with offsetting complications and early failures; these are being addressed through four procedural modifications. Restore valve shrinking, although conceptually attractive, is too problematic to be competitive with Closure treatment or saphenectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
89
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(93 citation statements)
references
References 26 publications
2
89
0
2
Order By: Relevance
“…Early results reported from a multicenter trial demonstrated a reasonable degree of success with an overall failure rate of 10% at a mean follow-up of 4.7 months (13% in patients treated with RF alone and 5% in patients treated with RF plus high ligation of the GSV). Complications included transient paresthesias (thigh, 9%; leg, 51%), skin burns (3%), deep venous thrombosis (3%), and one pulmonary embolus (24). More recent studies have demonstrated success rates of 73%-90% with follow-up to 24 months in 21 limbs (25)(26)(27).…”
Section: Discussionmentioning
confidence: 96%
“…Early results reported from a multicenter trial demonstrated a reasonable degree of success with an overall failure rate of 10% at a mean follow-up of 4.7 months (13% in patients treated with RF alone and 5% in patients treated with RF plus high ligation of the GSV). Complications included transient paresthesias (thigh, 9%; leg, 51%), skin burns (3%), deep venous thrombosis (3%), and one pulmonary embolus (24). More recent studies have demonstrated success rates of 73%-90% with follow-up to 24 months in 21 limbs (25)(26)(27).…”
Section: Discussionmentioning
confidence: 96%
“…Paresthesia was reported to occur in 9% to 19% of limbs within 1 week after the procedure [12][13][14][18][19][20][21][22][23][24][25][26][27], and gradually resolved over time [25]. Limiting treatment to the above-knee segment decreases the risk of paresthesia because 90% of the time the saphenous nerve travels within the saphenous compartment from the groin to the knee, and then travels superficial to this compartment, and thus is more susceptible to injury with heat in the below-knee location despite tumescent fluid infiltration.…”
Section: Radiofrequency Ablation Safetymentioning
confidence: 99%
“…To date, there have been over 100,000 RFA procedures performed worldwide, and its safety has been carefully reported [12][13][14]. Most impressively, a clinical registry was established in 1998 to monitor procedure safety and treatment outcomes.…”
Section: Radiofrequency Ablation Safetymentioning
confidence: 99%
“…Quando há comprometimento importante da veia safena, interna ou externa, a fleboextração do segmento acometido permanece sendo o tratamento de escolha [17][18][19][20][21][22][23] . Mais recentemente, a fotocoagulação da veia safena com o laser endovenoso aparece como uma alternativa menos invasiva do que a fleboextração convencional [24][25][26][27][28][29][30] .…”
Section: Discussionunclassified